Effects of epoxidation content of ENR on morphology and mechanical properties of natural rubber blended PVC - Jarunee Jeerupun (2018)
This research work has concerned a study on toughness of PVC/natural rubber (NR) blends compatibilized with epoxidized natural rubber (ENR). The aim of this work was to investigate the effect of degree of epoxidation on morphology and mechanical properties of the blends. Epoxidized natural rubber with a variety of epoxidation contents were prepared by reacting the NR latex with formic acid and hydrogen peroxide at various chemical contents. Chemical structure and epoxidation content of epoxidized natural rubber were evaluated by FTIR and1H-NMR techniques. After that, three grades of ENR with epoxidation contents of 15, 25 and 42% (by mole) were further used for blending with PVC and NR in an internal mixer at 60 rpm and at 170°C. From tensile and impact tests, it was found that tensile elongation and impact strength of the materials remarkably increased with degree of epoxidation. On the other hand, tensile strength and modulus of the materials rarely changed with the epoxidation content. An increase in toughness of the blends with epoxidation content was related to a better molecular interaction between PVC and ENR as suggested by torque-time curves of the materials.